Spiral growth mode in DMDPC organic thin film transistors by physical vapor deposition. Issue 56 (24th May 2016) - Liu, Tianjun; Wang, Jiawei; Wang, Liang; Wang, Jing; Lan, Jingbo; You, Jingsong; Jiang, Chao
Abstract : We report the observation of a screw-dislocation-driven spiral growth of DMDPC organic thin films. The existence of screw dislocations was clearly confirmed by the observations of outcropped stepsand spiral fringes. Abstract : We report the observation of a screw-dislocation-driven spiral growth of DMDPC organic thin films using physical vapor deposition. The existence of screw dislocations was clearly confirmed by the observations of outcropped steps, single monolayer height helical periodicity and spiral fringes.